P0965CAN EMPAGLIFLOZIN BE A CANDIDATE FOR THE ROLE OF A UNIVERSAL CARDIO- AND NEPHROPROTECTIVE DRUG IN CHRONIC HEART FAILURE WITHOUT DIABETES MELLITUS?. (6th June 2020) - Okovityy, Sergey; Ivkin, Dmitry; Krasnova, Marina; Karpov, Andrey; Ivanova, Galina; Beresneva, Olga; Kashina, Elena; Zaraiski, Mikhail; Galkina, Olga; Parastaeva, Marina; Khasun, Mokhamad; Kayukov,, Ivan; et al.
Abstract: Background and Aims: The multi-system nature of chronic heart failure (CHF) requires therapeutic approaches and medications that can have pleiotropic effects. For example, it is desirable that drugs for the treatment of CHF have direct cardio- and nephroprotective effects. These conditions are largely met by angiotensin converting enzyme (ACE) inhibitors and, possibly, inhibitors of the membrane sodium/glucose cotransporter (SGLT-2) inhibitors. The study aimed to investigate the effects of the SGLT2 inhibitor empagliflozin on CHF in normoglycemic rats. The effects of empagliflozin were compared with the standard medications for CHF - ACE inhibitor fosinopril, which has cardio - and nephroprotective effects in CHF. Method: Myocardial infarction (MI) was induced in male Wistar rats via permanent ligation of the left descending coronary artery. One-month post MI 30 animals were randomized into 3 groups (n=10): vehicle-treated, empagliflozin (1.0 mg/kg) and fosinopril (10 mg/kg). One month after surgery all medications administered per os daily for 3 months. Echocardiography, 24-hour urine volume test, albuminuria, proteinuria or miRNA-21 expression in urine and treadmill exercise tests (0.7 m/sec and the slope angle 15°) were performed at the beginning and at the end of the study. Results: At the finish of the study (4 months after MI - 3 months on treatment) all empagliflozin treated animals survived, one animal died in vehicle group and 3 animals in the fosinopril group. In vehicle group sizes of the left ventricle (LV) increased and the ejection fraction (EF) decreased in comparison with the initial values. Rats of fosinopril group confirm well known beneficial effect ACE inhibitors on cardiac remodeling and function; LV sizes and EF didn't change except 2 atrial dimensions enlargement. Treatment with empagliflozin slowed the progression of left ventricular dysfunction: LV sizes and EF didn't change and the minute volume significantly increased (from 52, 0±15, 5 ml/min to 61, 2±21, 2 ml/min) as compared to baseline. Moreover, empagliflozin exhibited maximal physical exercise tolerance in comparison with all groups (289 ± 27 sec versus 183 ± 61 sec in fosinopril group, p=0, 0035 for multiple comparisons). Recently, using this model of CHF in the normoglycemic rats we have found that SGLT2 inhibition for 3 months increased the tolerance to physical exercise. This effect was associated with an improvement of cardiac function as demonstrated by increased stroke volume, minute volume and LV ejection fraction as well as with the improvement of renal function. In rats of empagliflozin group 24-hour urine volume (9.8±0.92 ml) was slightly but not significantly higher than in the vehicle (6.9±1.25 ml) and in the fosinopril group (7.39±0.53 ml); p=0, 09 for multiple comparisons. So, it could be suggested that other mechanisms apart from SGLT2 inhibition in kidneys and decrease of the volume overload are involved in protective action of empagliflozin. In any case, due to increased water and sodium excretion empagliflozin treatment can lead to decreased cardiac preload . There were no significant differences in levels of albuminuria and proteinuria or miRNA-21 expression in urine in groups with and without empagliflozin. Conclusion: Sodium-glucose co-transporter 2 inhibitor empagliflozin reduced progression of left ventricular dysfunction and improved tolerance of physical exercise in normoglycemic rats with HF. Empagliflozin treatment compared with fosinopril was superior in respect of physical tolerance and not inferior in terms of nephroprotective action. Taking into account the obtained results one can be considered empagliflozin as a potential universal cardionephroprotector.